Nutritional evaluation of the lipid fraction of feral wild boar (Sus scrofa scrofa) meat. - Quaresma, M a G; Alves, Susana P; Trigo-Rodrigues, I; Pereira-Silva, R; Santos, N; Lemos, J P C; Barreto, a S; Bessa, R J B (Meat science, 2011)
Consumer increasing demand for wild boar meat and scarceness of data on its lipid fraction justified this study. The psoas major muscle collected from 25 feral wild boars was used to quantify the total lipid, total cholesterol, fatty acid (FA) profile, and vitamin E homologues. Intramuscular fat and total cholesterol contents averaged 4.64 g/100g of meat and 56.9 mg/100g of meat, respectively. No differences were found in FA composition between groups, except for 20:5n-3 that was higher in youngsters. All groups presented small concentrations of rumenic acid in meat (CLA; 0.24% of total FA). FA profile showed considerable resemblance with pork, while the vitamin E profile is marked by high concentrations of both alpha- (17.4 ± 3.3 μg/g meat) and gamma-tocopherols (2.6 ± 1.3 μg/g meat) and by the presence of other vitamin E homologues not previously reported in wild boar meat.
Keywords: Cholesterol; fatty acids; meat quality; Vitamin E; Wild boar

Seed bank composition and above-ground vegetation in response to grazing in sub-Mediterranean oak forests (NW Greece) - Chaideftou, Evgenia; Thanos, Costas a; Bergmeier, Erwin; Kallimanis, Athanasios; Dimopoulos, Panayotis (Plant Ecology, 2008)
We investigate the persistent soil seed bank composition and its relation to the above-ground ﬂora of grazed and non-grazed sub-Mediterranean deciduous oak forests of NW Greece. Twenty-eight taxa were recorded in the soil seed bank and 83 taxa (70 taxa in plots of seed bank sampling) in the aboveground vegetation. The dominant tree species and many woodland species found in the above-ground vegetation were absent from the soil seed bank. Similarity between the soil seed bank and the aboveground vegetation decreased with grazing, and grazing led to a decrease of species richness in above-ground vegetation and soil seed bank. Beta diversity of vegetation among grazed and among nongrazed plots did not differ, but was signiﬁcantly higher between grazed and non-grazed areas. Beta diversity of the soil seed bank declined with grazing. When applying classiﬁcation tree and logistic regression analyses, non-grazed forest sites are clearly differentiated by the presence of Phillyrea latifolia, Euphorbia amygdaloides and Brachypodium sylvaticum. PCA ordination of above-ground species composition reﬂected a gradient from sites grazed by ruminants to non-grazed sites, but no clear structure was detected in the seed bank.
Keywords: á ruminants; Deciduous oak forests; deciduous oak forests á; grazing á browsing á; Grazing Browsing; greece; greece á wild boar; Ruminants; Soil seed bank; soil seed bank á; Wild boar; Wood pasture; wood pasture á

Seed bank composition and above-ground vegetation in response to grazing in sub-Mediterranean oak forests (NW Greece) - Chaideftou, Evgenia; Thanos, Costas A.; Bergmeier, Erwin; Kallimanis, Athanasios; Dimopoulos, Panayotis (Plant Ecology, 2008)
We investigate the persistent soil seed bank composition and its relation to the above-ground ﬂora of grazed and non-grazed sub-Mediterranean deciduous oak forests of NW Greece. Twenty-eight taxa were recorded in the soil seed bank and 83 taxa (70 taxa in plots of seed bank sampling) in the aboveground vegetation. The dominant tree species and many woodland species found in the above-ground vegetation were absent from the soil seed bank. Similarity between the soil seed bank and the aboveground vegetation decreased with grazing, and grazing led to a decrease of species richness in above-ground vegetation and soil seed bank. Beta diversity of vegetation among grazed and among nongrazed plots did not differ, but was signiﬁcantly higher between grazed and non-grazed areas. Beta diversity of the soil seed bank declined with grazing. When applying classiﬁcation tree and logistic regression analyses, non-grazed forest sites are clearly differentiated by the presence of Phillyrea latifolia, Euphorbia amygdaloides and Brachypodium sylvaticum. PCA ordination of above-ground species composition reﬂected a gradient from sites grazed by ruminants to non-grazed sites, but no clear structure was detected in the seed bank.
Keywords: á ruminants; Deciduous oak forests; deciduous oak forests á; grazing á browsing á; Grazing Browsing; greece; greece á wild boar; Ruminants; Soil seed bank; soil seed bank á; Wild boar; Wood pasture; wood pasture á

Habitat effects and shooting techniques on two wild boar (Sus scrofa) populations in Spain and Portugal - Fernández-Llario, P; Mateos-Quesada, P; Silvério, A; Santos, P (Zeitschrift für Jagdwissenschaft, 2003)
In the last decades, wild boar (Sus scrofa) distribution has increased world-wide, the Iberian Peninsula being no exception. The wild boar now inhabits almost the entire Iberian territory, where today it is one of the most important big game species. In this paper, for the first time, bag analysis from two ecological different regions are presented and compared to the employed hunting techniques. One represents the well-preserved Mediterranean forests of south-western Spain, the other, located in the south of Portugal, is a farmland with interspersed forest areas. Our results indicate a stronger hunting intensity and also a higher wild boar population density in the Portuguese study areas. The stronger hunting intensity may result in a younger wild boar population. We also found considerable differences between the shooting techniques used in both regions and those employed in the north-east of the peninsula. It does therefore not seem advisable to directly compare bag statistics from different regions of the Iberian peninsula.
Keywords: habitats; Mediterranean; Populations; Portugal; shooting techniques; Spain; Sus scrofa; Wild boar

Habitat effects and shooting techniques on two wild boar (Sus scrofa) populations in Spain and Portugal - Fernandez-Llario, P.; Mateos-Quesada, P.; Silvério, A.; Santos, P. (Zeitschrift für Jagdwissenschaft, 2003)
In the last decades, wild boar (Sus scrofa) distribution has increased world-wide, the Iberian Peninsula being no exception. The wild boar now inhabits almost the entire Iberian territory, where today it is one of the most important big game species. In this paper, for the first time, bag analysis from two ecological different regions are presented and compared to the employed hunting techniques. One represents the well-preserved Mediterranean forests of south-western Spain, the other, located in the south of Portugal, is a farmland with interspersed forest areas. Our results indicate a stronger hunting intensity and also a higher wild boar population density in the Portuguese study areas. The stronger hunting intensity may result in a younger wild boar population. We also found considerable differences between the shooting techniques used in both regions and those employed in the north-east of the peninsula. It does therefore not seem advisable to directly compare bag statistics from different regions of the Iberian peninsula.
Keywords: habitats; Mediterranean; Populations; Portugal; shooting techniques; Spain; Sus scrofa; Wild boar

Cynegetical development of the French Mediterranean ``matorral'' scrublands: Case of wild ungulates - Maillard, D; Melac, O; Gaudin, J C; Vassant, J (GIBIER FANE SAUVAGE - GAME AND WILDLIFE, VOL 15 (SPECIAL NUMBER PTS 2 AND 3) 1998, 1998)
Since the beginning of the seventies, the marorrals (garrigues, maquis, and holly oak, Quercus ilex, copses) are slowly being colonized by roe deer, Capreolus capreolus, white wild boar; Sus scrofa, populations are stongly increasing. This phenomenon is mainly due to a relative low hunting pressure compared to the potential huntable population, to the disappearance of traditional farming practices (rural abandonment) causing the matorrals to extend, to the compensations paid to farmers since 1969, and to an increase in food resources (ageing of holly oak copses). As for red deer, Cervus elaphus, its population is increasing very slowly: The uncontrolled increase in wild boar populations is causing intolerable damages to farmers, especially in high-quality crops (arboriculture, vines, market-garden crops), which have been expanding since the productive lands in the bottom of the valley are being cultivated and agricultural techniques have improved. In the years to come, the ungulates frequenting the garrigue may become a harvestable resource if the two main sympatric species (wild boar and roe deer) which are occupying areas of some 30,000 ha, are wisely managed and the following parameters are taken into account : - amount of food produced in the habitats (annual mast crops); - damage control by controlled hunting in each massif, and damage prevention (protection or dissuation); - appropriate management of ungulate territories and the effective control of their populations based on hunting bag analyses in the middle and at the end of the hunting season. Most of ail it is important that before applying the ``population/environment/damage{''} model in each massif or management unit, clear management objectives be defined in agreement with the farmers.
IUGB XXIIIrd Congress, LYON, FRANCE, SEP 01-06, 1997
Keywords: roe deer; Sus scrofa; Wild boar; wild ungulate